Investigating the Impact of Nitrogen Addition in Growing Media using Liquid Organic Fertilizer on Pigment and Protein Content of Spirulina sp. - Saffana, Nadhira; Wijihastuti, Risa Swandari; Noriko, Nita (EXSACT-A, 2023)
Spirulina sp. is a highly promising microalgae with substantial protein and pigment content, holds great economic potential across various industries. However, the cultivation of Spirulina sp. often faces the challenge of high production costs, particularly in media formulation. To address this issue, the development of more affordable alternative media formulations is crucial. One potential approach involves utilizing a combination of liquid organic fertilizer derived from Canna indica waste and urea for cultivation. This study aims to determine the optimal ratio of the fertilizers mixture that influences protein and pigment synthesis. The study design employed a completely randomized design with seven treatment groups along with the control. The result shows that the treatment 2A (20 mL/L organic fertilizer; 125 ppm urea) demonstrated the highest dry biomass weight. Treatment 2C (22 mL/L organic fertilizer; 150 ppm urea) exhibited the best specific growth rate and carotenoid production, with the carotenoid production significantly differing from the control. Treatment 1A (20 mL/L organic fertilizer; 100 ppm urea) yielded the highest levels of chlorophyll and phycobiliproteins. Treatment 1B (20 mL/L organic fertilizer; 125 ppm urea) resulted in the highest protein production.